2019
DOI: 10.21203/rs.2.15583/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Undiagnosed Hypertension and Associated Factors among Adult Dwellers in Hawela Tula Sub City, Hawassa, Southern Ethiopia: A Community Based Cross-sectional Study

Abstract: Introduction Hypertension is a common public health problem and often goes unnoticed and can lead to a stroke or heart attack. It contributes to the high burden of cardiovascular disease, premature mortality, reduced quality of life and high costs to the health care system, especially in low and middle-income countries. Therefore, this study aimed to assess the prevalence of undiagnosed hypertension and influencing factors with health-seeking behaviour.Method A community-based cross-sectional study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
8
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 14 publications
11
8
3
Order By: Relevance
“…Respondents who did not perform regular physical exercise were 2.91 times more likely to have undiagnosed hypertension than those respondents who perform regular physical exercise. This finding was supported by the previous study conducted in Hawassa [ 42 ]. Physical exercise can prevent blood pressure by reducing blood vessel stiffness [ 53 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Respondents who did not perform regular physical exercise were 2.91 times more likely to have undiagnosed hypertension than those respondents who perform regular physical exercise. This finding was supported by the previous study conducted in Hawassa [ 42 ]. Physical exercise can prevent blood pressure by reducing blood vessel stiffness [ 53 ].…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, the result of this study is higher than studies conducted in the Byblos, Lebanon 16.9% [13], in India 10.1% [37], in United States of America 19.7% [38], in Iran 4.8% [21], in Ghana 18.5% [39], in Hosanna 10.2% [40], in Addis Ababa 13.25% [41] and Hawassa 12.3% [42].…”
Section: Discussioncontrasting
confidence: 76%
“…The prevalence of Unscreened hypertension in this study is comparable with the recent study in India(10.1%), Nigeria(14.6%) (17,18) and other study conducted in Ethiopia country wide (15.6%), Hawela-Tula sub-city(12.3%),Gulale,(13.25%),Hosanna(10.2%) (9,10,19,20)and it is higher when compared to study done in USA(6.5%) and Gilgal-gibe eld research (7.5%) (21,22).The variation might be due to the difference in screening strategy the country undertaking for the study in the USA and difference in the population studied (i.e. lower age cut-off used as compared to present study) for the Gilgal gibe study.…”
Section: Discussionsupporting
confidence: 88%
“…This study showed that those adults having a family history of Hypertension were 3.1 more likely to have unscreened hypertension. This might be due to the fact that hypertension tends to run among families(31).This nding is similar to the study done in Ethiopia (9).…”
Section: Discussionsupporting
confidence: 87%
“…Population and sample size -Those Adults aged 19 to 65 years living in the rural areas Dano district were included in the study whereas, those Adults who were previously diagnosed with hypertension , those screened for hypertension in the last year, pregnant mothers and mothers in post-partum periods were excluded from the study. The sample size was determined by considering factors that are significantly associated with the outcome variable from previous study (10) using two-sided confidence level of 95%, power 80% and the ratio of exposed to unexposed 1:1 for each factors, using Epi Info Version 7.2.2.6. Then, by considering, 1.5-design effect the final sample size was 605.…”
Section: Methodsmentioning
confidence: 99%